2009
DOI: 10.1148/radiol.2511080666
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic Fatty Liver Disease: Diagnostic and Fat-Grading Accuracy of Low-Flip-Angle Multiecho Gradient-Recalled-Echo MR Imaging at 1.5 T

Abstract: Relaxation- and interference-corrected fat quantification at low-flip-angle multiecho GRE MR imaging provides high diagnostic and fat-grading accuracy in NAFLD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
424
3
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 300 publications
(444 citation statements)
references
References 53 publications
14
424
3
3
Order By: Relevance
“…The influence of J-coupling on established T 2 values for lipids has been acknowledged (11,18,21,35), and to minimize its affect on calculated T 2 , STEAM (stimulated echo acquisition mode) (36), or PRESS sequences with a range of short TEs were employed (7,11,18,21). In this work we applied a technique, previously employed to rewind the scalar coupling evolution of lipid methyl protons at 3 T (26), to the 2.1 ppm lipid allylic protons, to the 2.3 ppm lipid protons in a position to the carbonyl group, and to the 2.8 ppm lipid diallylic protons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of J-coupling on established T 2 values for lipids has been acknowledged (11,18,21,35), and to minimize its affect on calculated T 2 , STEAM (stimulated echo acquisition mode) (36), or PRESS sequences with a range of short TEs were employed (7,11,18,21). In this work we applied a technique, previously employed to rewind the scalar coupling evolution of lipid methyl protons at 3 T (26), to the 2.1 ppm lipid allylic protons, to the 2.3 ppm lipid protons in a position to the carbonyl group, and to the 2.8 ppm lipid diallylic protons.…”
Section: Discussionmentioning
confidence: 99%
“…LIPID MEASUREMENTS by proton magnetic resonance spectroscopy (MRS) have been useful in understanding a number of disorders, including diabetes (1-3), obesity (3)(4)(5), liver disease (6,7), and cancer (3,(8)(9)(10). It has been suggested that there may be a link between the composition of fatty tissue and the risk of suffering from such diseases (11,12).…”
mentioning
confidence: 99%
“…86 Table 3 presents results of the imaging techniques used in diagnosis of NAFLD-NASH. 86,[90][91][92][93][94][95][96][97][98][99][100][101][102][103][104][105][106][107][108][109] The underlying physical principle of imaging techniques are the same between adults and children. Consequently research in both age groups could be used to approve the use of these methods in pediatric field.…”
Section: Image Studiesmentioning
confidence: 99%
“…101 Liver stiffness measurement by transient elastography is a reliable method for predicting significant liver fibrosis. [102][103][104][105][106][107][108] Discordance of transient elastography with liver pathology may be related to unsatisfactory liver biopsy specimen. 101 Magnetic resonance offers imaging and spectroscopic methods for quantification of fat with relatively high accuracy without any invasive procedures or radiation exposure.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…On in-phase images, the signal intensity difference between lobes is likely to be smaller. Advanced MR imaging techniques that are designed to simultaneously assess fat and iron accumulation are now being developed (16,17). These techniques are likely to facilitate the diagnosis of lobar fat accumulation that is superimposed over iron overload; however, these techniques are not yet commercially available.…”
Section: Fat Accumulationmentioning
confidence: 99%